Redimensionamento e análise térmica de equipamento de secagem contínua utilizando princípios fundamentais de transferência de massa e calor - Groff, Juliano Katayama (2015)
Analyze the gelatin drying equipment, resizing and its evaluation based on the thermal mass and heat transfer phenomena. Industrially, equipaments are developed and marketed, its methods and criteria are not disclosed and each company has its characteristics for the operation of such equipment, often based only on trial and error. In order to evaluate this method and make this useful intermediation are proposed in a systematic manner, criteria and assumptions for assessing dryer track-type gelatin starting from laboratory tests in batch equipment at 30, 40, 52, 60, 70 and 80 oC until the moisture balance, their mass and energy balances for each camera, resizing the equipment simulating the speed of the treadmill 6 m/h, 12 m/h, 18 m/h and 24 m/h, all its features and also a thermal analysis. In order to validate the method and propose improvements for future projects of the same device with the same function, a comparison of industrial data equipment operated for several years was performed. The proposed method shows the possibility of increasing speed up to 18 m/h with an error of at most 31.6% to the final moisture, the impossibility of initial drying at temperatures above 52°C and using the energy balance approaching the gelatin as a hollow cylinder. Thus, it is possible the use of laboratory analysis as a means of optimization of this equipment as well as a future alternative to operating improvements and design.